Contribution to the taxonomy of the Hylaeus gibbus species group in Europe (Hymenoptera, Apoidea and Colletidae) - Straka, Jakub; Bogusch, Petr (Zootaxa, 2011)
We redescribe and present new diagnoses of the Hylaeus gibbus group in Europe. Species of this group were often confused with each other. Our method of distinguishing between the species is based on dividing three commonly recognised species into four. We present diagnoses and list the characteristics of Hylaeus confusus Nylander, 1852; Hylaeus gibbus Saunders, 1850; and Hylaeus pictus (Smith, 1853). For the newly characterised form, one of Förster’s available names has been resurrected—Hylaeus incongruus Förster, 1871. Hylaeus gibbus occurs only in southern Europe and northern to southern parts of central Europe, while H. incongruus reaches more northern latitudes. Types of the most problematic and poorly described forms were examined. Some names of clearly lost types were fixed by designating neotypes.